Expression and posttranslational modification of class III beta-tubulin during neuronal differentiation of P19 embryonal carcinoma cells. - Laferrière, Nicole B. (University of Ottawa (Canada), 1996)
The functional significance of Class III $\beta$-tubulin during neurogenesis has been investigated. A combination of northern blotting, immunofluorescence microscopy, enzyme-linked immunosorbent assay, and isoelectric focusing was used to characterize the expression of $\beta$-III tubulin in P19 embryonal carcinoma cells induced to differentiate along a neuronal pathway retinoic acid. Following 48 hours differentiation, $\beta$-III tubulin mRNA is evident and $\beta$-III tubulin appears in the mitotic spindle of neuronal precursors. Neurite outgrowth is obvious by day and $\beta$-III tubulin and mRNA levels increase concurrently until approximately day 8, when $\beta$-III mRNA levels begin to decrease while protein levels remain high. In addition, increasingly acidic $\beta$-III isoforms appear with days of differentiation. The accumulation of these isoelectric variants occurs concomitant with a temporal increase in the incorporation of $\beta$-III tubulin into colchicine-stable microtubules. P19 cells were grown on coverslips and then treated with taxol concentrations from 10$\sp{-6}$ M to 10$\sp{-9}$ M for 24 hours. The microtubule cytoskeleton was examined after double-immunofluorescence labelling with a monoclonal antibody to $\alpha$-tubulin (YOL 1/34) and a monoclonal neuron-specific $\beta$-III tubulin antibody (TuJ1). Treatment of undifferentiated P19 cells with concentrations of taxol greater than 4 X 10$\sp{-8}$ M causes microtubule bundling and multiple aster formation and promotes polymerization the low levels of $\beta$-III tubulin found in these cells. In neurons, at 2 X 10$\sp{-8}$ M taxol, bundling of microtubules at the base the neurite is apparent. At taxol concentrations greater than 10$\sp{-7}$ M enhanced assembly of $\beta$-III tubulin is noted, although long neurites are not observed. An additional isoform of $\beta$-III tubulin is detected following treatment with 10$\sp{-6}$ M taxol. These results indicate that taxol treatment alters the normal subcellular sorting tubulin isotypes, promotes the polymerization and translational modification of $\beta$-III tubulin, and interferes with neurite outgrowth. The coding sequence of mouse $\beta$-III tubulin was transiently expressed in undifferentiated P19 cells and its assembly and resistance to colchicine-depolymerization examined by immunofluorescence microscopy and isoelectric focusing. Two $\beta$-III tubulin isoforms are detected on isoelectric focusing immunoblots. Microtubule disassembly by colchicine appears identical in the transfected and adjacent non-transfected cells. The results reveal that Class III $\beta$-tubulin is assembly competent and can undergo at least one posttranslational modification in non-neuronal cells. Several posttranslational modifications of $\beta$-III tubulin have been identified, including phosphorylation of Ser$\sp{444}$ and/or Tyr$\sp{437}$, and glutamylation of Glu$\sp{438}$. Of these, phosphorylation of Ser$\sp{444}$ is unique to $\beta$-III tubulin in brain. To investigate the role of Ser$\sp{444}$ phosphorylation of $\beta$-III tubulin, site-directed mutagenesis was used to generate two mouse $\beta$-III tubulin mutants. In one, Ser$\sp{444}$ was replaced by Ala$\sp{444}$ to provide a $\beta$-III tubulin molecule which could not undergo phosphorylation at that site. In the second mutant, Ser$\sp{444}$ was replaced by Glu$\sp{444}$ to mimic a constitutively phosphorylated protein. When $\beta$-III tubulin Ser$\sp{444}$ mutant expression vectors are transiently expressed in P19 cells, examination reveals that both mutant $\beta$-III tubulins yield labelling patterns which are similar to the wild-type $\beta$-III tubulin. Neither $\beta$-III tubulin mutation confers resistance to 45 min colchicine-induced depolymerization in non-neuronal cells. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.